Photokinetics of Photothermal Reactions - Mounir Maafi (Molecules)
Photothermal reactions, involving both photochemical and thermal reaction steps, are the most abundant sequences in photochemistry. The derivation of their rate laws is standardized, but the integration of these rate laws has not yet been achieved. Indeed, the field still lacks integrated rate laws for the description of these reactions’ behavior and/or identification of their reaction order. This made difficult a comprehensive account of the photokinetics of photothermal reactions, which created a gap in knowledge. This gap is addressed in the present paper by introducing an unprecedented general model equation capable of mapping out the kinetic traces of such reactions when exposed to light or in the dark. The integrated rate law model equation also applies when the reactive medium is exposed to either monochromatic or polychromatic light irradiation. The validity of the model equation was established against simulated data obtained by a fourth-order Runge–Kutta method. It was then used to describe and quantify several situations of photothermal reactions, such as the effects of initial concentration, spectator molecules, and incident radiation intensity, and the impact of the latter on the photonic yield. The model equation facilitated a general elucidation method to determine the intrinsic reaction parameters (quantum yields and absorptivities of the reactive species) for any photothermal mechanism whose number of species is known. This paper contributes to rationalizing photokinetics along the same general guidelines adopted in chemical kinetics.